Proposta de adaptação de cicloergômetro e os efeitos de sua aplicação no treinamento de membros superiores na capacidade funcional e de exercício e na qualidade de vida em pacientes com DPOC - Gonzaga, Luana Aparecida Vieira (Universidade Federal de São Carlos, 2021)
Exercise intolerance can affect upper limbs (upper limbs) and lower limbs (lower limbs) differently, with the upper limbs' muscle function being relatively preserved as they are more frequently used in routine activities of daily living (ADL), including personal hygiene or involvement of some of these muscles in breathing work. Despite the relative preservation of the function of the upper limbs muscles, it is common to complain of dyspnea on the part of patients with COPD when performing activities with the limb without support, that is, at or above the shoulders without support. One of the treatments indicated is endurance training, as for example on the arm cycle ergometer. The MMSS training in an arm cycle ergometer allows, by keeping the distal end of the limb supported, that the scapular waist musculature can assist in breathing, prolonging the duration of the exercise and delaying the onset of dyspnea. Despite the benefits such as improved exercise tolerance, quality of life and reduced dyspnea, this method has been passed over to training without support,. Patients with COPD and functional disability may have a greater tolerance for training without support when performing an adaptation period with the upper limbs training on a cycle ergometer, thus regaining their independence. However, there is difficulty regarding its use, since cycle ergometers with the necessary characteristics (measurement of load and cadence, and height adjustment) for the application of training with MMSS support are expensive and generally inaccessible to clinics and patients. Therefore, this study aims to propose a cycle ergometer adapted for upper limbs (article 1) and to verify the effects of its use on upper limbs training of COPD patients (article 2). To adapt the cycle ergometer of article 1, the Mini Bike PRO E13 from Acte Sports® was attached to a table with height adjustment plus a torque wrench on the right crank and a cadence sensor on the table. The study included the participation of patients of both genders, with a clinical and spirometric diagnosis of COPD who underwent an Incremental Exercise Test (IET) on the cycle ergometer adapted until exhaustion. Obtaining as results the evaluation of 13 individuals with COPD, (FEV1 / FVC: 0.50 ± 3.4), 67 ± 3 years, BMI 24 ± 4.14, irregularly active and active. The IET lasted an average of 9 minutes, reaching a maximum load of 4.5 N.m on average, with VO2max reached 0.80 ± 0.25 l/min, equivalent to 36 ± 12% of the predicted. We concluded that the equipment was able to assess the functional capacity when reproducing a submaximal IET in patients with COPD. In article 2, an experimental study was carried out, such as a randomized controlled clinical trial in a controlled block, blind evaluator and parallel group, using the MMSS cycle ergometer adapted in article 1. The training protocol lasted a total of 8 weeks, three times a week, 50 minutes each session. Patients were divided into Intervention (IG) and Control (CG) groups. Both started the sessions with stretching of the main muscle groups, followed by heating for three minutes with no load on the MMSS cycle ergometer at a 70 rpm without load. In the IG, they performed another 30 minutes with a load of 70% of the work rate found in the incremental upper limb test and ended with three minutes of cooling down without load. In the CG, all training on the cycle ergometer was carried out without load. To test the exercise capacity, IET and constant load test (CLT) were performed, to verify the functional capacity, the six minute pegboard and ring test (6-PBRT) and the TGlittre were performed, and to verify the health-related quality of life Saint George Respiratory Questionnaire (SGRQ) is applied. The IG obtained better results after the intervention than the CG in the physical tests IET load (+0.91), IET VO2 (+0.20), CLT time (+ 3min), and only the IG reached the minimum important difference in the CLT (+1.75 min). Both groups reached the minimum important difference in Glittre (GC -38 sec; GI -30 sec). Despite not having found statistical relevance, the present study showed that MMSS training in the proposed adapted cycle ergometer tends to be effective in improving physical capacity and functional status.
Proposed adaptation of a cycle ergometer and the effects of its application in upper limb training on functional and exercise capacity and quality of life in patients with COPD
Keywords: Terapia por exercício; Extremidade superior; Teste de esforço; Doença Pulmonar Obstrutiva Crônica (DPOC); Exercise therapy; Upper extremity; Stress test; Chronic Obstructive Pulmonary Disease (COPD); CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL